Examination of Molecular Effects of MYLK Deletion in a Patient with Extensive Aortic, Carotid, and Abdominal Dissections That Underlie the Genetic Dysfunction. (22nd June 2020) - Macklin, Sarah K.; Bruno, Katelyn A.; Vadlamudi, Charitha; Helmi, Haytham; Samreen, Ayesha; Mohammad, Ahmed N.; Hines, Stephanie; Atwal, Paldeep S.; Caulfield, Thomas R.
Abstract : We describe the phenotype of a patient with extensive aortic, carotid, and abdominal dissections. The proband was found to have a heterozygous deletion of exons 21–34 in MYLK, which is a rare finding, as deletions in this gene have been infrequently reported. We describe this finding following detection in a proband with an extensive history of aortic, carotid, and abdominal dissections. Neoteric molecular modeling techniques to help determine the impact of this deletion on protein function indicated loss of function due to lack of any kinase domain. We also provide the electrostatics calculations from the wild type and mutant variant. Through a combined multiomic approach of clinical, functional, and protein informatics, we arrive at a data fusion for determination of pathogenicity embedded within the genetic code for this particular genetic variant, which, as a platform, continues to broaden its scope across the field of variants of uncertain significance classification.